An observational study of the 'isolated forearm technique' in unparalysed, spontaneously breathing patients. - Pandit, J (Wiley, 2015)
The isolated forearm technique enables a patient, otherwise paralysed by neuromuscular blockade, to communicate by movement if wakeful during surgery. The positive response rate to verbal command is high (~32%). The 5th National Audit Project recommended that this monitoring technique should become more widely taught and considered, so this study was designed to assess its utility as a standard of care in unparalysed patients. A positive response rate as high as in the paralysed would justify local adoption. Therefore, 100 consecutive patients undergoing urology surgery were given verbal commands to move at two-minute intervals from induction of anaesthesia (fentanyl and propofol) to full emergence and extubation of the supraglottic airway. Anaesthesia was maintained with isoflurane in oxygen/nitrous oxide. Although 24 patients moved during surgery (and therefore needed additional anaesthetic), none moved to verbal command. Even at extubation, when patients moved to expel the airway, there was no response to command until after wakening. These results suggest that in contrast to its use in paralysed patients, the isolated forearm technique does not yield useful information about the patient’s state of wakefulness in the unparalysed. Another interpretation is that unparalysed patients are less prone to wakefulness than the paralysed.